CS-28 Validation of remission and lupus low disease activity stateas predictors of organ damage in SLE. (August 2018) - Petri, Michelle; Goldman, Daniel; Magder, Laurence S
Abstract : Background: Outcome measures that combine control of SLE activity and prednisone reduction are clinically relevant. A clinical goal in SLE is to reduce risk of long-term organ damage. We assessed whether two recently proposed disease activity outcomes were predictive of future damage. Methods: For each month of follow-up in a large SLE cohort, we determined whether the patient was in Clinical Remission (as defined by the DORIS working group) or lupus low disease activity state (LLDAS) (as defined by Franklyn et al). Clinical Remission was defined as a PGA<0.5, clinical SLEDAI=0 and no prednisone or immunosuppressants. Clinical Remission on Treatment allowed for prednisone ≤5 mg/day and immunosuppressant use. LLDAS was defined as a SLEDAI ≤4, PGA≤1.0, no major organ activity, and no new activity. LLDAS on treatment allowed for prednisone use ≤7.5 mg/d and immunosuppressants. Damage was defined using the SLICC/ACR Damage index. Results: There were 81 118 person-months observed among 2026 patients (92% female, 53% Caucasian, 39% African-American). Table 1 shows the rates of damage, per person month, in subgroups defined by Remission or LLDAS. Damage rates were relatively low when LLDAS was achieved at least 50% of the time. These rates were similar to those experienced by patients who met a more stringent treatment restriction with Remission on Treatment at least 50% of the time. Conclusions: Percent time in LLDAS had a clear dose response for rate ratios of organ damage. Even 25% of time in remission reduced organ damage. LLDAS on treatment >50% of the time, which led to a 50% reduction in organ damage, is an easier goal to achieve (3 times more person-months observed in our cohort) and more realistic as a clinical trial outcome. Acknowledgements: The Hopkins Lupus Cohort is funded by NIH AR 43727 and NIH AR 69572.